Does the 45 mm Size Cutoff for Ascending Aortic Replacement Predict Better Early Outcomes in Bicuspid Aortic Valve? - Li, Yi-Jia; Ma, Wei-Guo; Qi, Yue; Zhu, Jun-Ming; Yang, Ya; Sun, Li-Zhong (The Thoracic and Cardiovascular Surgeon, 2021)
Background The aim of this study is to test if the newly proposed 45 mm size criterion for ascending aortic replacement (AAR) in bicuspid aortic valve (BAV) patients undergoing aortic valve replacement (AVR) is predictive of improved early outcomes.Methods Data of 306 BAV patients with an aortic diameter of ≥45 mm undergoing AVR alone or with AAR were retrospectively analyzed. Patients were divided into groups of AVR + AAR (n = 220) and AVR only (n = 86) based on if surgery was performed according to the 45 mm criterion. End point was early adverse events, including 30-day and in-hospital mortality, cardiac events, acute renal failure, stroke, and reoperation for bleeding. Cox regression was used to assess if conformance to 45 mm criterion could predict fewer early adverse events.Results AVR + AAR group had significantly higher postoperative left ventricular ejection fraction (LVEF) (0.59 ± 0.09 vs. 0.55 ± 0.11, p = 0.006) and longer cardiopulmonary bypass (CPB) time (128 vs. 111 minutes, p = 0.002). Early adverse events occurred in 45 patients (14.7%), which was more prevalent in the AVR-only group (22.1% vs. 11.8%, p = 0.020). Conformance to the 45 mm criterion predicted lower rate of early adverse events (hazard ratio [HR]: 0.53, 95% confidence interval [CI]: 0.28–0.98, p = 0.042). After adjustment for gender, age, AAo diameter, sinuses of Valsalva diameter, preoperative LVEF, Sievers subtypes, BAV valvulopathy, and CPB and cross-clamp times, conformance to the 45 mm size criterion still predicted lower incidence of early adverse events (HR: 0.37, 95% CI: 0.15–0.90, p = 0.028).Conclusions This study shows that conformance to 45 mm size cutoff for preemptive AAR during aortic valve replacement in patients with BAV was not associated with increased risk for adverse events and may improve early surgical outcomes.
Keywords: bicuspid aortic valve; ascending aorta; surgery; aortic valve replacement; surgical outcomes